ХРОНОТОП ДОРОГИ В ПРОЗЕ В.Г.КОРОЛЕНКО - Ivanova, Oxana (İdil : sanat ve dil dergisi, 2016)
In the paper the road chronotope is connected with three years of forced staying of V.G. Korolenko in Yakutia in 1881-1884 and with the writer’s trip to America in 1893. In the story “Makar’s Dream” (1885), as well as in the novel “Without Language” (1895), the time is unidirectional, the events are depicted in logical and chronological sequence but the simultaneous events and actions occurring in different places are not depicted. In “Makar’s Dream” the reader is placed into a fantastic dream area where he has the possibility to watch the character go to inimical taiga first, where even the hares mock him, and then, after Makar’s “faint” readers follow the traveling of his soul to another world. In the American texts of V.G. Korolenko the duality of the country writer’s perception can be seen. From the one hand, America in the novel “Without Language” is presented as a mythological infernal space, the hell, in the plot structure a mythological formula of the “death” and the following “resurrection” of the character is used by the author and the guest house of Mister Bork gets some characteristics of the “antihouse”. From the other hand, in the process the character of the novel Matvey Lozinskiy begins to discern the advantages of America and the exotic foreign land starts to demonstrate its human sides.